Citizen identity formation of domestic students and Syrian refugee youth in Jordan: Centering student voice and Arab Islamic ontologies - Daniel Shephard (Journal of Social Science Education)
Patricia Kubow (2003). Citizen identity formation of domestic students and Syrian refugee youth in Jordan: Centering student voice and Arab Islamic ontologies. New York: Routledge. ISBN 9781003143215